Cultural Diplomacy through Hallyu: Managing Bilateral Relations between South Korea and Indonesia - Amalia, Nurul (Jurnal Ilmiah Manajemen Kesatuan, 2023)
South Korea’s cultural diplomacy has permeated and become a phenomenon among the younger generation in Indonesia. The issue of culture as an instrument in conducting diplomacy has become a global phenomenon that attracts the attention of many countries. This phenomenon illustrates the use of cultural aspects as a means to achieve diplomatic goals, implement policies, and shape a country’s attitude towards others. The significance of cultural influence in diplomacy goes beyond material aspects, encompassing normative and ideational dimensions of a nation. The use of culture as an instrument in diplomacy is not unidirectional, where one country tries to influence another. Instead, it involves exchange and mutual influence between different cultures, creating a framework for more inclusive and sustainable cooperation. The research methodology employed in this study is descriptive qualitative analysis. Descriptive qualitative analysis focuses on a deep understanding of a phenomenon or event, leading to descriptive data interpretation. Data for this research is sourced from information released by the governments of South Korea and Indonesia, as well as South Korean cultural centers. The study is implemented using theories within the field of International Relations. Data collection techniques involve literature review, interviews, and online data searches. Hallyu, as an expression of popular South Korean culture, has created a strong allure among Indonesian society, facilitating cultural exchange, ideas, and information between nations. Cultural diplomacy through Hallyu has proven to be an effective tool in strengthening relations between South Korea and Indonesia. However, caution, transparency, and close cooperation among involved parties are necessary to mitigate risks and safeguard the national interests of each country in effectively and sustainably conducting cultural diplomacy.